2006
DOI: 10.1002/cmdc.200500042
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioate Analogues of Alkyl Lysophosphatidic Acid as LPA3 Receptor‐Selective Agonists

Abstract: The metabolically stabilized LPA analogue 1-oleoyl-2-O-methyl-rac-glycerophosphorothioate (OMPT) was recently shown to be a potent subtype-selective agonist for LPA3, a G-protein-coupled receptor (GPCR) in the endothelial differentiation gene (EDG) family. Further stabilization was achieved by replacing the sn-1 O-acyl group with an O-alkyl ether. A new synthetic route for the enantiospecific synthesis of the resulting alkyl LPA phosphorothioate analogues is described. The pharmacological properties of the alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…6A, right). We next examined the potencies of nine synthetic LPA analogs as p2y5 agonists and found that the LPA 3 -selective agonist alkyl-OMPT (26,27) had agonistic activity almost equal to or slightly higher than 1-oleoyl-LPA (Fig. 6B).…”
Section: Adenylyl Cyclase Activation By P2y5 Through a G S/13 Chimericmentioning
confidence: 99%
“…6A, right). We next examined the potencies of nine synthetic LPA analogs as p2y5 agonists and found that the LPA 3 -selective agonist alkyl-OMPT (26,27) had agonistic activity almost equal to or slightly higher than 1-oleoyl-LPA (Fig. 6B).…”
Section: Adenylyl Cyclase Activation By P2y5 Through a G S/13 Chimericmentioning
confidence: 99%
“…14 Thus, great efforts have been made on the study of LPA receptor antagonists and agonists due to their therapeutic potential. [15][16][17][18][19][20][21] In aggregate, these data suggest that ATX is an attractive pharmacological target; blockage of LPA production via ATX inhibition by small molecules could be a useful anticancer chemotherapy. 22,23 A lead towards developing ATX inhibitors was provided by the discovery that this enzyme undergoes end product inhibition by, for example, LPA 24 .…”
mentioning
confidence: 99%
“…LPA 6 /p2y5 showed a preference for 2-acyl LPA over 1-acyl LPA [19] . Alkyl-OMPT, an LPA 3 agonist, and 2-linoleoyl LPA showed better agonistic effects on the LPA 6 receptor than 2-oleoyl LPA showed [19,64] . In contrast, the methyl ester of LPA (LPM) was shown to be a pan-agonist for LPA [1][2][3][4][5] although it was less potent than LPA [65] .…”
Section: Lpa Gpcr Agonistsmentioning
confidence: 99%
“…As mentioned above, VPC01091 is an orally active S1P 1 agonist and S1P 3 antagonist [87] . W146, hexyl phenyl amide phosphonate, was found to Ki16425 [70] Antagonist Antagonist Antagonist (250 nmol/L) (5600 nmol/L) (360 nmol/L) DGPP [69] Antagonist Antagonis (6600 nmol/L) (106 nmol/L) VPC32183 [67] Antagonist Antagonist (109 nmol/L) (175 nmol/L) VPC12249 [66] Antagonist Antagonist (137 nmol/L) (428 nmol/L) 2-Pyridyl phosphonate [68] Antagonist Thiophosphatidic acid 8:0 [54] Antagonist Antagonist (360 nmol/L) (5 nmol/L) T14 [58] Antagonist NSC161613 [72] Antagonist (24 nmol/L) Compound 12 [120] Antagonist Antagonist (48 nmol/L) (230 nmol/L) H2L5186303 [72] Antagonist Antagonist (7.2 nmol/L) (310 nmol/L) 5987411 [55] Antagonist Antagonist (741 nmol/L) (1300 nmol/L) 5765834 [55] Antagonist Antagonist (48 nmol/L) (292 nmol/L) α-bromomethylene Antagonist Antagonist Antagonist Antagonist Weak agonist phosphonate [52,55,73,117] (751 nmol/L) (304 nmol/L) (380 nmol/L) (167 nmol/L) Tetradecyl-phosphonate [43] Antagonist Antagonist Antagonist (10000 nmol/L) (5500 nmol/L) (3100 nmol/L) Farnesyl diphosphate [55,71] Antagonist Antagonist Antagonist Agonist (2100 nmol/L) (155 nmol/L, (1980 nmol/L) (40 nmol/L) 4600 nmol/L) Carba cyclic PA [55] Agonist OMPT [49] Agonist (68 nmol/L) Alkyl OMPT [19,64] Agonist Agonist Agonist (790 nmol/L) (62 nmol/L) α-fluoromethylene Weak agonist Weak agonist Agonist phosphonate [51] (0.5 nmol/L) α-hydroxymethyleneAgonist phosphonate [52] (393 nmol/L) Compound 8bo [121] Agonist Agonist (9.1 nmol/L) (123 nmol/L) Dialkyl thiophosphatidic Agonist Agonist Agonist Agonist acid 8:0 [54,55] (695 nmol/L) (5720 nmol/L) (3 nmol/L) Antagonist Antagonist (382 nmol/L) (184 nmol/L) Dodecylphosphate [56] Agonist Antagonist (700 nmol/L) (90 nmol/L) α-methylene Agonist Weak agonist Agonist phosphonate [52,…”
Section: S1p Gpcr Antagonistsmentioning
confidence: 99%